Beyond Traditionalism: Media Technology and the Digital Transformation of Nahdlatul Ulama Boarding School - Sunaryanto; Ahmad Falhan; Ahmad Adnan (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study focuses on analyzing the role of media technology in the development of Nahdlatul Ulama (NU) Islamic boarding schools (pesantren). It employs an extensive literature review of journal articles, undergraduate theses, master's theses, dissertations, and relevant online sources. The study is conducted within the paradigm of da'wah communication. The collected data were analyzed using the interactive data analysis model developed by Miles and Huberman. The findings reveal that digital media technology has transformed areas of conflict and institutional development, including shifting the traditional social role of the kyai toward a more gender-inclusive model. Women in NU Islamic boarding schools are increasingly provided with broad access to digital media skills and knowledge, enabling them to contribute to boarding school development. Furthermore, the development of NU Islamic boarding schools should continue to be strengthened through the convergence of digital media and technological innovation. The construction of NU Islamic boarding schools demonstrates that digital media technology can serve as a productive space by integrating traditional Islamic values with modern technological practices. In this regard, media technology is utilized to build a positive digital presence that supports the promotion of da'wah and Islamic education.